Pyrolysis of water buffalo manure: Influence of temperature and alkali hydroxide additives on the quality of bio-oil. (November 2021) - Özbay, Günay; Koçak, Ebru; Ahmad, Muhammad Syarhabil
Abstract: In this study, the influence of catalytic and non-catalytic pyrolysis of the water buffalo manure on the physical-chemical characterizations, pyrolysis product yield and chemical composition of bio-oil was studied. The first part of the experiments was performed in a reactor with a diameter of 24 mm and height of 36 cm, running with varying temperature from 350 °C to 550 °C. The highest yield of bio-oil was found 27.6 wt% at 450 °C. After optimum temperature was determined, effects of alkali hydroxides catalysts were investigated. Under the influence of NaOH and KOH used as alkali hydroxide, a reduction in liquid product yield was recorded, while an increase was observed on char and gas yield. The obtained results from elemental analysis depicted that the H/C ratios increased while O/C ratios decreased under the influence of alkali hydroxides catalysts. 1 H NMR analysis results showed that aliphatic OH groups constitute the majority of pyrolysis bio-oil. The chemical characterization of bio-oil was conducted by gas chromatography-mass spectrometry (GC-MS). Alkali hydroxides catalysts had important effect on the chemical content, especially hydrocarbons and carboxylic acids. When the catalysts applied, the percent of hydrocarbons increased, on the other hand the percent of carboxylic acids decreased. This research study revealed the potential of bio-oil obtained from water buffalo pyrolysis can be used as a renewable energy source. Highlights: We evaluate the effect of the temperature and alkali hydroxides catalysts on the bio-oil. The existence of alkali hydroxides as a catalyst was notably increased the carbon amount in the bio-oil. Water buffalo manure bio-oil has common functional groups and chemicals related to phenols. Hydrocarbon content increased under the effect of alkali hydroxides catalysts, while acid content decreased.